PENGARUH KINERJA LINGKUNGAN, MANAJEMEN LABA, DAN MEDIA EXPOSURE TERHADAP CSR DISCLOSURE - Nurul Haidah (2021)
This study aims to examine the effect of environmental performance, earnings management, and media exposure on corporate social responsibility disclosure. The population in this study is companies listed on the Indonesia Stock Exchange in the period 2017 - 2019. The sampling technique using a purposive sampling method and found 25 samples of companies. Hypothesis testing in this study is multiple linear regression. Based on multiple linear regression analysis and t test shows that environmental performance, earnings management, and media exposure have no effect on CSR disclosure.